Foraminiferal stratigraphy in the Plio-Pleistocene Kap Kebenhavn Formation, North Greenland - Feyling-Hanssen, Rolf W. (Meddelelser om Grønland. Geoscience, 1991)
Fossil foraminiferal assemblages occurring in fine-grained sediments of the Kap København Formation, Peary Land, North Greenland, are grouped into six assemblage zones: the Elphidium funderi Zone, oldest, the Cassidulina laevigata Zone, the Elphidiella rolfi Zone, the Elphidium cf. excavatum Zone, the Elphidium excavatum Zone, and the Elphidiella gorbunovi Zone, youngest. Comparison of these zones with fossil foraminiferal assemblages from other Arctic localities and with fossil assemblages from borings in the North Sea indicates that the Elphidium funderi Zone and the Cassidulina laevigata Zone are of Upper Pliocene age whereas the Elphidium excavatum Zone belongs to the Lower Pleistocene. The Elphidiella rolfi Zone is an uppermost Pliocene shallow water zone, and the Elphidium cf. excavatum Zone probably.